Determination of Tear and Serum Inflammatory Cytokines in Patients with Rosacea Using Multiplex Bead Technology. (3rd June 2013) - Topcu-Yilmaz, Pinar; Atakan, Nilgun; Bozkurt, Banu; Irkec, Murat; Aban, Demet; Mesci, Lutfiye; Tezcan, Ilhan
Abstract: Purpose : To compare serum and tear inflammatory and anti-inflammatory cytokine levels of rosacea patients with the healthy controls and evaluate the correlation of tear cytokine levels with tear function parameters. Methods : Tear and serum interleukin (IL)-1α, IL-6, IL-8, IL-10, monocyte chemotactic protein-1 (MCP-1), macrophage inflammatory protein-1α (MIP-1α), epidermal growth factor (EGF), and vascular endothelial growth factor (VEGF) levels were measured using multiplex bead (Luminex) technology in 12 rosacea patients without ocular involvement (group 1), 20 rosacea patients with ocular involvement (group 2), and 22 healthy subjects (group 3). The correlation of the cytokines with tear function parameters was analyzed using Spearman correlation test. Results : Tear IL-10 and VEGF levels were significantly lower in group 1 (median: 35.78 pg/mL and 427.29, respectively) and group 2 (median: 26.25 pg/mL and 348.31, respectively) than in group 3 (median: 75.96 pg/mL and 480.12, respectively) ( p  < 0.05). Mean serum IL-8 level was significantly lower in group 2 (median = 0) compared to group 3 (median = 3.98) ( p  = 0.02). Tear breakup time was found to be positively correlated with IL-10 ( r  = 0.46, p  = 0.013) and inversely correlated with MCP-1 ( r  = −0.52, p  = 0.004). Conclusions : Tear and serum levels of cytokines and growth factors measured with Luminex technology showed a large variation in rosacea and healthy subjects. Decreased levels of tear IL-10, an anti-inflammatory cytokine, may lead to an inflammatory ocular surface environment, exacerbate ocular surface inflammation, and deteriorate tear function tests. A bigger sample size, including rosacea patients with corneal involvement, is needed to confirm the role of cytokines in the pathogenesis of rosacea-associated ocular inflammation.